Cockayne Syndrome: A rare neurodegenerative disorder- A case report - Dola, Farah Naz; Kundu, Gopen Kumar; Miah, Quddus; Sarker, Anita (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Cockayne Syndrome (CS) is a rare autosomal recessive disorder characterised by multi-systemic involvement, including developmental delay, microcephaly, cachectic dwarfism, hearing and visual impairment, cardiac, renal and endocrine complications due to a defect in the DNA repair mechanism. The striking feature of CS is bilateral basal ganglia calcifications. We are presenting a 9-month-old boy presenting with developmental delay, microcephaly, multiple renal abnormalities and the brain CT scan showing bilateral basal ganglia calcifications. J Bangladesh Coll Phys Surg 2025; 43: 303-305